2001
DOI: 10.1111/j.1469-7793.2001.0271g.x
|View full text |Cite
|
Sign up to set email alerts
|

State‐dependent hyperpolarization of voltage threshold enhances motoneurone excitability during fictive locomotion in the cat

Abstract: Electrical stimulation of the brainstem in paralysed decerebrate cats evokes a centrally generated pattern of motor output (fictive locomotion) that has many of the characteristics of overground locomotion in adult quadripedal mammals (see Rossignol, 1996). During fictive locomotion, motoneurones innervating limb muscles receive alternating excitatory and inhibitory synaptic currents from the central pattern generator (CPG) for locomotion (Jordan, 1983). These result in the rhythmic fluctuations of membrane po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
138
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(156 citation statements)
references
References 19 publications
16
138
2
Order By: Relevance
“…Further analysis of repetitive firing during MLR-induced fictive locomotion demonstrated that the voltage threshold for initiation of APs is hyperpolarized compared to resting conditions (Krawitz et al, 2001). In a subsequent modeling study, this hyperpolarization was readily accounted for by modulation of the fast inactivating sodium current (Dai et al, 1998).…”
Section: State-dependence Of Motoneuron Properties: Modulation Duringmentioning
confidence: 95%
See 1 more Smart Citation
“…Further analysis of repetitive firing during MLR-induced fictive locomotion demonstrated that the voltage threshold for initiation of APs is hyperpolarized compared to resting conditions (Krawitz et al, 2001). In a subsequent modeling study, this hyperpolarization was readily accounted for by modulation of the fast inactivating sodium current (Dai et al, 1998).…”
Section: State-dependence Of Motoneuron Properties: Modulation Duringmentioning
confidence: 95%
“…Once alternating locomotor activity began, however, the firing rate increased to the pre-adapted frequency, indicating a "reversal" of late SFA. If late SFA is mediated by a long time constant of inactivation of fast sodium channels (Section 7), then the Krawitz et al (1996) data, together with the data indicating hyperpolarization of voltage threshold (Krawitz et al, 2001), may indicate modulation of these channels during locomotor activity. Finally, if late SFA is related to fatigue (Kernell and Monster, 1982a;Gandevia, 2001), then modulating (reducing) this property during locomotion may enable the animal to sustain locomotor activity for lengthy periods of time.…”
Section: State-dependence Of Motoneuron Properties: Modulation Duringmentioning
confidence: 99%
“…However, our simulations indicate these other effects would not counteract the effects of changes in PIC amplitude on discharge hysteresis and ⌬F values. For example, neuromodulators have been shown to lower spike threshold (e.g., Fedirchuk and Dai 2004;Krawitz et al 2001). Our simulations indicate that raising spike threshold through increases in accommodation reduces ⌬F values; thus lowering spike threshold should enhance the effects of neuromodulatory drive on ⌬F.…”
Section: Using ⌬F To Estimate Changes In Neuromodulationmentioning
confidence: 97%
“…For each neuron, an average of the spike shape and following inter-spike interval profile was obtained by averaging successive spontaneous spikes taken either at the resting membrane potential or while the cell was slightly depolarized (for the few neurons that were silent at rest). The spikes (mean number of ϳ120) were synchronized to their thresholds, taken at the point on the rising phase of the action potential where the slope of the potential trace reached an arbitrary threshold of 10 V/s (Krawitz et al 2001). The averaged spike shape was used to determine the amplitude of the afterhyperpolarization (AHP) and the width of the spike (taken at threshold).…”
Section: Basic Membrane and Firing Properties Of Mvnnmentioning
confidence: 99%